Experimental evidence of parasite-induced behavioural alterations modulated by food availability in wild capuchin monkeys - Agostini, Ilaria (2023)
In disease dynamics, host behaviour can both determine the quantity of parasites a host is exposed to, and be a consequence of infection. Observational and experimental studies in non-human primates have consistently found that parasitic infections result in less movement and reduced foraging, which was interpreted as an adaptive response of the host to counter infection. Variation in host nutritional condition may add complexity to the infection-behaviour relationship, and its influence may shed light on its significance. To experimentally evaluate how host activity and social relationships are affected by the interaction of parasitism and nutrition, during two years we manipulated food availability by provisioning bananas, and helminth infections by applying antiparasitic drugs, in two groups of wild black capuchin monkeys (Sapajus nigritus) in Iguazú National Park, Argentina. We collected faecal samples to determine the intensity of helminthic infections, as well as data on behaviour and social proximity. Individuals with unmanipulated helminth burdens foraged less than dewormed individuals only when food provisioning was low. Resting time was increased when capuchins were highly provisioned, but it did not vary according to the antiparasitic treatment. Proximity associations to other group members were not affected by the antiparasitic treatment. This is the first experimental evidence of a modulating effect of food availability on the influence of helminth infection on activity in wild primates. The findings are more consistent with an impact on host behaviour due to the debilitating effect caused by parasites than with an adaptive response to help fight infections.